Design guidelines and usability for cognitive stimulation through technology in Mexican older adults. (2nd January 2022) - Acosta, Christian O.; Palacio, Ramón R.; Borrego, Gilberto; García, Raquel; Rodríguez, María José
ABSTRACT: To develop software to stimulate cognitive functions of attention, memory, reasoning, planning, language, and perception in Mexican older adults, and to evaluate the usability of software based on system utility, information quality, and interface quality. For the development of the cognitive stimulation software, an inductive-deductive methodology was used in three stages: Analysis (system requirements), design and coding (cognitive stimulation software), evaluation (usability results). The usability of the software was assessed in 89 older adults between the ages of 60 and 84 years, through a usability questionnaire with evidence of reliability and validity. Eight exercises about attention, seven on memory, three on reasoning, one about planning and language, and two on perception were developed. We evaluated the usability of the developed software using the Computer System Usability Questionnaire, obtaining medium-high usability in 76.2% of the participants regarding the system utility, in 77.7% concerning the information quality and, in 84.2% in the interface quality. The software was developed considering aspects of usability and based on changes and losses associated with aging, as well as on the stimulation of cognitive functions related to instrumental activities of daily living, including exercises based on traditional pencil-paper exercises.